Students’ voice: a needs analysis of University General English Course in Iran - Moiinvaziri, Marjan (Penerbit UKM, 2014)
Needs analysis is an important step in terms of developing curriculum and syllabus for different courses. It is necessary to become familiar with students‟ objectives, attitudes, learning habits and expectations of the course in order to have an appropriate and suitable syllabus and course design. This study was an attempt to investigate the perceived English language needs of students in university General English course in Iran. This is an obligatory three-credit course offered for all non-English majors, for which no specialized syllabus is proposed by the Ministry of Education and as a result different teachers would select different syllabuses, methods and textbooks based on their own beliefs and experiences while hardly considering students‟ real needs and wants. In order to detect students‟ views toward what they need to learn, their preferred learning style, and their attitudes, motivation and interest toward learning English, a revised version of questionnaire developed by Sihong (2007) was utilized. The results revealed that the students considered vocabulary as the most important component of the language which needed the most practice, whereas they found grammar as the component that they most resented and had the least expertise in. In addition, they perceived reading as the most important skill, while they considered listening and speaking as their most problematic skills. The students also showed positive attitudes and high motivation toward learning English. It is hoped that findings from this study can assist Iranian teachers and curriculum and syllabus designers to consider the importance of the students‟ real needs and try to develop and design materials which can fulfill the present gap.